2009
DOI: 10.1007/s10803-009-0751-2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Independence in Autism Spectrum Disorders: A Review of Three Focused Interventions

Abstract: The features of autism that inhibit the independent demonstration of skills, as well as three effective interventions for increasing independence, are explored in this review article. Independent performance may prove difficult for individuals with autism spectrum disorders (ASD) due to the core deficits of the disability, as well as executive function deficits that impact initiation and generalization. These difficulties, coupled with intervention strategies that encourage over-reliance on adult support, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(164 citation statements)
references
References 56 publications
(72 reference statements)
2
161
0
1
Order By: Relevance
“…Prompt dependence is often a major concern when teaching students with ASD and ID. VM is an intervention that may require less adult prompting strictly based on intervention procedures (Hume et al, 2009). …”
Section: Intervention Variations and Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prompt dependence is often a major concern when teaching students with ASD and ID. VM is an intervention that may require less adult prompting strictly based on intervention procedures (Hume et al, 2009). …”
Section: Intervention Variations and Descriptionsmentioning
confidence: 99%
“…Shockingly, Giangreco and Broer (2005) reported that special education paraprofessionals reported spending 86% of their day within 3 feet of their assigned student. One of the most appealing potential advantages of VM is that the intervention may provide opportunities for students with ASD and ID to work more independently (Hume et al, 2009). …”
Section: Potential Advantages Of Vmmentioning
confidence: 99%
See 1 more Smart Citation
“…Hygiene, in general, and self-care routines can be a challenge for people with ASD, and targeted instruction will need to be coupled with supports to make sure that routines are implemented. Visual supports, such as visual schedules of the steps required to complete hygiene routines and reminders of when to initiate routines, will be necessary for many patients with ASD [18]. Sex education should include how and when to clean one's genitals, when to seek medical attention, including for sexual symptoms, and whom to consult.…”
Section: Physical Well-being In Relation To Sexualitymentioning
confidence: 99%
“…While these strategies are necessary in providing the acquisition of skills, strategies that promote independence should also be addressed. The most common research based interventions (Ryan, Hughes, Katsiyannis, McDaniel, & Sprinkle, 2010) to increase independence for students with an ASD include structured work systems (Carnahan et al, 2009;Hume et al, 2009;Panerai et al, 2009;Schopler, 1994), self-monitoring King-Sears, 2006;King-Sears & Carpenter, 2005;Lee, Poston et al, 2007;Lee, Simpson et al, 2007), social stories (Adams, Gouvousis, Van Lue, & Waldron, 2004;Agosta, Graetz, Mastropieri, & Scruggs, 2004;Barry, & Burley, 2004;Brownell, 2002;Gray & Garand, 2003;Kuoch & Mirenda, 2003), video modeling (Charlop-Christy, Le, & Freeman, 2000;Cihak, Fahrenkrog, Ayres, & Smith, 2010;Delano, 2007;Dowrick, 1999;Maione & Mirenda, 2006;McCoy & Hermansen, 2007;Nikopoulos & Keenan, 2003), and video self modeling Bellini, Akullian, & Hopf, 2007;Buggey, 2005;Buggey, 2007;Hitchcock, Dowrick, & Prater, 2003).…”
Section: Interventions Used With Individuals With Asd For Children Wmentioning
confidence: 99%